Situación actual de las franquicias internacionales de comida rápida en la ciudad de Barranquilla (2016)
The next investigation has as an objective to describe the current situation of the international fast food franchises in Barranquilla. To get it, is necessary to explain the concept of franchise, its theoretic approach, its generalities, and the concept of fast food. It identifies the background of the arrival to the city of the different companies. It describes the consumption of fast food in the different franchises based on the gathered information from the polls made to consumers; and finally, it describes the model of the international fast food franchises in the city based on the interviews applied to people in each company, whose questions were made based on the ontology of business models proposed by Alexander Osterwalder. With the gathered information and based on the findings of the investigation we can conclude the arrival of these companies was accelerated in the last years, mainly by the economic development of the city and by the high preference for fast food of the consumers from Barranquilla, turning the city in a potential market and with many opportunities for all of these companies, that with their arrival created more job opportunities and generated an increase in the levels of consumption of this type of food.